2014
DOI: 10.1039/c3cp54817a
|View full text |Cite
|
Sign up to set email alerts
|

Study by electrical conductivity measurements of semiconductive and redox properties of M-doped NiO (M = Li, Mg, Al, Ga, Ti, Nb) catalysts for the oxidative dehydrogenation of ethane

Abstract: Pure and M-doped nickel oxides with M = Li, Mg, Al, Ga, Ti, Nb, catalysts for the oxidative dehydrogenation of ethane into ethylene, were characterized by in situ electrical conductivity measurements. Their electrical conductivity was studied as a function of temperature and oxygen partial pressure and was followed with time during sequential exposures to air, an ethane-air mixture (reaction mixture) and pure ethane under conditions similar to those of catalysis. All the materials appeared to be p-type semicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 30 publications
4
26
0
Order By: Relevance
“…It can be observed that the activation energy of conduction is significantly lower for all the oxides beyond the Néel temperature. At the same time, for both temperature ranges considered, the E c values were higher for all Nb(x)NiO samples compared to the NiO reference, as already observed for NiO doped with higher valent cations 26,36 and presents only small differences between the Nb(x)NiO systems. pure NiO at this temperature.…”
Section: Variations Of the Electrical Conductivity As A Function Of Tsupporting
confidence: 79%
See 2 more Smart Citations
“…It can be observed that the activation energy of conduction is significantly lower for all the oxides beyond the Néel temperature. At the same time, for both temperature ranges considered, the E c values were higher for all Nb(x)NiO samples compared to the NiO reference, as already observed for NiO doped with higher valent cations 26,36 and presents only small differences between the Nb(x)NiO systems. pure NiO at this temperature.…”
Section: Variations Of the Electrical Conductivity As A Function Of Tsupporting
confidence: 79%
“…11,12 A useful and highly sensitive technique to characterize the electronic and redox properties of oxidation catalysts is the electrical conductivity measurement, 13 a large number of papers having been dedicated to this subject in the last decade. [14][15][16][17][18][19][20][21][22][23][24][25][26] Numerous previous studies have correlated the electrical conductivity of the oxide materials with their catalytic performance in ODH reactions of ethane into ethylene, 19,[26][27][28] propane into propene, [29][30][31] n-butane into butenes and butadiene 32,33 and isobutane into isobutene. 17,20 NiO is a p-type semiconducting oxide containing an excess of lattice oxygen anions associated with the existence of positive holes as main charge carriers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supported catalysts (NiO-based [8,9] and VO x -based [10][11][12] metal oxide catalysts) and unsupported catalysts (NiWO x -based [13], NiNbO x -based [14][15][16][17], NiSnO x -based [18], and MoVO x -based metal mixed oxide catalysts [19,20]) both show high activity in the ODHE reaction at a relatively low temperature (<500°C). Among all the catalytic systems above, a mixed metal oxide catalyst, MoVNbTeO x , is one of the most outstanding catalysts for ODHE [21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was assigned to electron transfer enhancement played by Nb, leading to easier activation of the C-H bond of ethane (see above Section 4.2 & Figure 11 from [67]). Other promoters such as Zr, which acts as a Lewis acid, but also Mg, Li, Ga, Ti, Ta, [96] or alumina have also been proposed for NiO catalyst to increase ethylene yield.…”
Section: Case Of Ethanementioning
confidence: 99%